Hz. Ömer’in miras ilmindeki görüşleri karşılaştırmalı çalışma - Salayma, Bushra (My University, 2020)
Çalışmamızda Hz. ömer’in miras ilmindeki nakil edilen görüşleri ele alacağız, ayrıca çalışmamızda Hz. ömer’in miras ilimindeki kulandığı yönetimi aktıracağız.Hz. ömer’in miras ilmindeki bırkatığı izleri açıklamalanması ve Hz. ömer’in görüşlerinden diğer sahâbenin görüşlerine nasıl etkileniğini ortaya koyacağız. Daha sonra Hz. ömer’in miras ilmindeki görüşleri tâbiîn ve ehl-i sünnetin dört mezhebin aynı meselerde ki görüşlerini aktıracağız, bu görüşleri Hz. ömer’in görüşlerini ona kim katılıp katılmadığını yada değer sahâbe Hz. Ali bin Ebu Talib, Hz. Zeyd bin Sabit, ve Hz. Abdullah bin Mesud gibi görüşlerini alıp almadığını ortaya koymaktadır. Çalışmamızda, Peygamberimiz ve Hz. Ebu Bekir dönemindeki ve Hz. Ömer’in dönem’indeki miras ilimnideki ortaya çıkan yeni meseleri ele alacağız.Bu meselerinden; dedenin mirası, Ömeriyyeteyn Meselesi, Ömeriyye Meselesi. Hz. Ömer’in ve diğer sahâbe bazı meseleri görüşlerini ihatlaf olduğu için tabiîn ve ehl-I süünet dört mezhep kitaplarında aynı meselide farklı görüşleri rastlanmaktadır.Çalışmamızda kulandığımız yöntem şu şekilde bildirebiliriz: ilk önce meseleyi genel tantım yaparak sonra Hz. Ömerin görüşünü açıklayıp görüşüne katılan değer sahâbe ve tabiî de zekir edildi, daha sonra Hz. Ömerin görüşüne karşı çıkan sahâbe ve tabiîn görüşlerin açıklayarak dört mezhep görüşlerini aktarılmıştır, sonra dört mezhebin delillerini değerlendirmeyi ele alınmıştır.

This study addresses the issues of the science of inheritance that transmitted from Caliph Omar Ibn Al-Khattab (May Allah be pleased with him), clarifying his approach in dealing with inheritance issues while monitoring the impact of his perspectives on the opinions of the companions. And to what extent the jurisprudential opinions of the Followers and the opinions considered in the four schools of jurisprudence either follow-up to the sayings of Omar Ibn Al-Khattab or not follow- up with it, but Follow-up with the sayings of other companions like Ali Ibn Abi Talib, Zayd Ibn Thabit, and Abdullah Ibn Masud (May Allah be pleased with all of them). Besides, clarifying the opinions of Omar Ibn Al-Khattab regarding inheritance issues that don’t have equivalent at the time of the Prophet (peace and blessings be upon him) or the caliphate period of Abu Bakr Al-Siddiq (May Allah be pleased with him), such as the age issue, the two age issues, and the attempt to place a share for grandfather in inheritance despite the absence of either explicit Qur’anic texts or authentic Hadith in that issue. Further, the difference of opinions between Omar Ibn Al-Khattab and some of the Companions had a significant impact on the variation of the sayings in the four schools of jurisprudence, and even in the opinions of the Followers.Accordingly, in this study, I will initially give a general definition of the issue meaning. Then I will mention the opinion of Omar Ibn Al Khattab (May Allah be pleased with him) about it, and whoever followed him from the companions and the followers as well. Afterward, I will mention the opinions of dissenters, followed by the opinions of the four schools of jurisprudence, and which opinion they choose concerning the issue raised. Then I will mention their evidences and finally discuss it.
Keywords: Caliph Omer; Ferâiz; Hz. Ömer; Islam; Islamic law; inheritance; İslam; İslam hukuku; Miras